Educate cadres for the prevention of Covid-19 in Sei Mati Village, Medan Maimun District - Lubis, Rahayu; Jemadi; Rasmaliah (Talenta Publisher, 2021)
The first case of Covid-19 in Indonesia was in early March 2020 and continues to grow until December 13, 2020, reaching 617 820 positive for Covid-19 and 18,819 deaths. Data in North Sumatra Province, there are 16,682 positive Covid-19 and 640 deaths and Medan City statistical data there are 8192 people positive for Covid-19 and 327 died. Prevention of Covid-19 transmission needs to be done by involving cadres, therefore this service aims to form health cadres and provide educational packages on the prevention of Covid-19 transmission in Sei Mati Village, Medan Maimun District. The reason for choosing the location was because cadres played an active role in their environment. Participants are health cadres such as posyandu cadres. The method used to measure knowledge using a questionnaire before and after the intervention (pre and post test design). The intervention was in the form of lectures and questions and answers using in-focus followed by videos. The implementation of community service was carried out in the Sei Mati village head office hall on September 26, 2020. Participants who attended were 25 people with an average age of 36 years. There was an increase in knowledge and efforts to prevent Covid-19 by 14.7% after intervention. Regular outreach efforts to the community are needed about efforts to increase immunity and maintain health protocols and the availability of running water for washing hands to avoid Covid-19 transmission. The output of this service is in the form of journal articles, educational videos and newspaper publications.